Opposing Effects of Ubiquitin Conjugation and SUMO Modification of PCNA on Replicational Bypass of DNA Lesions in Saccharomyces cerevisiae - Haracska, Lajos (American Society for Microbiology, 2004)
The Rad6-Rad18 ubiquitin-conjugating enzyme complex of Saccharomyces cerevisiae promotes replication through DNA lesions via three separate pathways that include translesion synthesis (TLS) by DNA polymerases ζ (Polζ) and Polη and postreplicational repair mediated by the Mms2-Ubc13 ubiquitin-conjugating enzyme and Rad5. Here we report our studies with a proliferating cell nuclear antigen (PCNA) mutation, pol30-119, which results from a change of the lysine 164 residue to arginine. It has been shown recently that following treatment of yeast cells with DNA-damaging agents, the lysine 164 residue of PCNA becomes monoubiquitinated in a Rad6-Rad18-dependent manner and that subsequently this PCNA residue is polyubiquitinated via a lysine 63-linked ubiquitin chain in an Mms2-Ubc13-, Rad5-dependent manner. PCNA is also modified by SUMO conjugation at the lysine 164 residue. Our genetic studies with the pol30-119 mutation show that in addition to conferring a defect in Polζ-dependent UV mutagenesis and in Polη-dependent TLS, this PCNA mutation inhibits postreplicational repair of discontinuities that form in the newly synthesized strand across from UV lesions. In addition, we provide evidence for the activation of the RAD52 recombinational pathway in the pol30-119 mutant and we infer that SUMO conjugation at the lysine 164 residue of PCNA has a role in suppressing the Rad52-dependent postreplicational repair pathway.